The Use of Fuzzy Assessment Models in the Evaluation of Financial Risks Concerning Mergers and Acquisitions in the Decision Making Process - Hanpiyavatanasakul, Sirinchar (2009)
This paper uses fuzzy assessment models in the evaluation of financial risks concerning mergers and acquisitions in the decision making process.